Natriuretic peptides modulate monocyte-derived Langerhans cell differentiation and promote a migratory phenotype - Horváth, Dorottya; Pénzes, Zsófia; Molnár, Petra; Rebenku, István; Vereb, György; Szántó, Magdolna; Muzsai, Szabolcs; Szegedi, Andrea; Dajnoki, Zsolt; Pázmándi, Kitti; Fekete, Tünde; Bácsi, Attila; et al. (Frontiers in immunology, 2025)
The interaction between the nervous and immune systems is crucial for maintaining homeostasis and can influence disease progression in inflammatory skin diseases, such as atopic dermatitis (AD). Sensory neurons in the skin can secrete neuropeptides that modulate immune cell activity, including Langerhans cells (LCs), one of the primary antigen-presenting cells in the epidermis. In our study we investigated the effects of neuropeptides on the differentiation of monocyte-derived LCs (moLCs), specifically the neuropeptides with the most profound effect, i.e. atrial- and B-type natriuretic peptides (ANP and BNP, respectively). RNA sequencing and RT-qPCR were used to analyze neuropeptide receptor expression in moLCs and immature dendritic cells (iDCs), and the most translationally relevant, natriuretic peptide receptor A (NPR1) was validated on the protein level using western blotting. Cell surface markers of moLCs were assessed using flow cytometry, and NPR1 functionality was confirmed through intracellular cGMP assays. Confocal microscopy was used to confirm the expression of NPR1 in healthy and AD skin. RNA-Seq analysis was also employed to characterize the phenotypic changes in moLCs differentiated in the presence of BNP. NPR1 expression was significantly higher in moLCs compared to iDCs, and treatment with ANP and BNP enhanced moLC differentiation, increasing CD207, CD1a, and HLA-DQ expression, while other tested neuropeptides (calcitonin gene-related peptide [CGRP], neurotensin) had no significant effect. NPR1 was functionally active, as evidenced by increased intracellular cGMP levels upon ligand binding. Confocal microscopy revealed NPR1 expression on LC cell bodies in both healthy and AD skin, with reduced intensity in AD. RNA-Seq analysis of BNP-treated moLCs indicated a shift toward a migratory LC phenotype, marked by upregulation of genes associated with cell motility (e.g., CCR7, LAMP3). These findings demonstrate that NPR1 activation promotes a migratory LC phenotype, highlighting the role of neuropeptides in shaping cutaneous immune responses. The reduced number of LCs in AD skin suggests a potential link between neuropeptide signaling and disease pathology.